Identification and Characterization of Conjugative Transposons CTn86 and CTn9343 in Bacteroides fragilis Strains - Buckwold, Simy L. (American Society for Microbiology, 2007)
The related genetic elements flanking the Bacteroides fragilis pathogenicity island (PAI) in enterotoxigenic B. fragilis (ETBF) 86-5443-2-2 and also present in pattern III nontoxigenic B. fragilis (NTBF) NCTC 9343 were defined as putative conjugative transposons (CTns), designated CTn86 and CTn9343, respectively (A. A. Franco, J. Bacteriol. 181:6623-6633, 2004). CTn86 and CTn9343 have the same basic structures except that their encoded transposases have low similarity and CTn9343 lacks the B. fragilis PAI and contains an extra 7-kb region not present in CTn86. In this study, using DNA hybridization and PCR analysis, we characterized the genetic element flanking the PAI in a collection of ETBF strains and the related genetic elements in a collection of NTBF pattern III strains. We found that in all 123 ETBF strains, the PAI is contained in a genetic element similar to CTn86. Of 73 pattern III strains, 26 (36%) present a genetic element similar to CTn9343, 38 (52%) present a genetic element similar to CTn9343 but lack the 7-kb region that is also absent in CTn86 (CTn9343-like element), and 9 (12%) present a genetic element similar to CTn86 but lacking the PAI (CTn86-like element). In addition to containing CTn86, ETBF strains can also contain CTn9343, CTn9343-like, or CTn86-like elements. CTn86, CTn9343, CTn86-like, and CTn9343-like elements were found exclusively in B. fragilis strains and predominantly in division I, cepA-positive strains.